Review of Alleged Abuse of Google Play Billing's Dominant Position in Indonesia: A Study of South Korea's Anti-Google Law - Afifah Afiyani. Y (Jurnal Indonesia Sosial Teknologi, 2024)
The author examines how the Anti-Google Law is implemented in South Korea and whether the law can be a solution for Indonesia in preventing giant digital platforms from abusing their dominant position. To review the alleged abuse of the dominant position of Google Pay Billing in Indonesia and conduct a study of the implementation of the Anti-Google Law in South Korea. This study uses doctrinal legal research methods through document and literature studies. The research results: For now, there have been several cases related to digital platforms that have entered ICC, such as GoTo in 2022, Google, and Shopee, which are about to enter the trial. It can be seen that there has been an increase in incoming cases related to digital platforms in ICC, therefore ICC must issue rules both in the form of laws, or technical regulations in the form of guidelines to regulate digital platforms, so that in the future.